Cybersecurity in Ukraine: current challenges and ways to improve legislative regulation - Mazepa , Svitlana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The modern realities of the digital transformation of society make it critically important to ensure cybersecurity as a key element of the state's national security. Ukraine, in conditions of permanent confrontation with hybrid threats and active digitalization of state and private structures, is faced with the need to form an effective system of legal regulation in the field of cyber defense. This study is aimed at a comprehensive analysis of the current state of legislative support for cybersecurity in Ukraine and identifying priority areas for its improvement.The relevance of the study is due to the rapid development of information and communication technologies, the increase in the number and sophistication of cyber attacks, as well as the need to adapt national legislation to European cybersecurity standards. The analysis of modern cyber threats demonstrates their cross-border nature, a high degree of coordination and the use of advanced technologies to cause damage to critical infrastructure, state institutions and the private sector. Special attention is paid to the study of the specifics of cyberterrorism, information operations and attacks on critical infrastructure in the context of modern geopolitical challenges.The methodological basis of the study includes a comprehensive approach to the analysis of regulatory legal acts, international agreements and the practice of their implementation into national legislation. The methods of comparative law, system analysis and empirical methods of research into the practice of law enforcement in the field of cybersecurity were used. Special attention is paid to the study of the experience of the European Union countries in the field of legal regulation of cyber protection and the possibilities of its adaptation to Ukrainian realities.The results of the study indicate the presence of significant gaps in the current legislation of Ukraine on the regulation of cybersecurity, including insufficient coordination between various state bodies, the absence of clear mechanisms for responding to cyber incidents and the inadequacy of sanctions for cyber offenses. Problems in the field of personal data protection, ensuring the security of critical information infrastructure and international cooperation in the field of countering cybercrime were identified. It was established that the existing regulatory framework does not fully meet the modern challenges of the digital age and requires comprehensive reform.The practical significance of the study lies in the development of specific recommendations for improving the legislative regulation of cybersecurity in Ukraine, including proposals for creating an integrated system of cyber protection, improving mechanisms for interagency interaction and increasing the effectiveness of countering cyber threats. Models of legal regulation adapted to the specifics of the Ukrainian legal system and compatible with international cybersecurity standards are proposed.Prospects for further research are related to the need for constant monitoring of the evolution of cyber threats and the appropriate adaptation of the legislative framework, the development of mechanisms for public-private partnership in the field of cybersecurity, as well as an in-depth study of the impact of artificial intelligence and new technologies on the system of legal regulation of cyber defense. An important direction is also the study of the role of international cooperation in the formation of the global cybersecurity architecture and the place of Ukraine in this system.